Nutritional diagnosis and length density distribution of fine roots in Acacia mangium Willd. - Pascual-Córdova, Guillermina; Palma-López, Jesús David; Obrador-Olán, José Jesús; García-López, Eustolia; Carrillo-Ávila, Eugenio; Sánchez-Soto, Saúl; Córdova-Sánchez, Alberto (Ecosistemas y Recursos Agropecuarios, 2023)
The acacia (Acacia mangium Wiild.) generates a large amount of aerial biomass, part of it, the litter, constitutes an important source of nutrients that are extracted from the depth of the soil by the root biomass, responsible for supporting the plant, absorption of nutrients and water. Based on the above, the objective of this research was to evaluate the edaphic fertility at the beginning, at 6 and 42 months of age of the acacia and the behavior of the vertical distribution of fine roots (DLRF) in a sugarcane soil converted to agroecosystem A. mangium at 6, 12, 18, 24, 30, 36 and 42 months of age, with two fertilization treatments. The nutritional diagnosis of the soil at the beginning showed favorable characteristics for the optimal development of the acacia, mostly medium contents. The nutrients Nt, P, K, Ca, Mg, had a statistically significant increase as age increased. The DLRF tended to be higher at 0-20 and 20-40 cm, in recent months it reached 2.0 km m−3, similar to that reported in other studies in the region, however, there was no statistically significant difference in its increase. due to fertilization effect, except at 42 months. Acacia shows a high potential to increase soil fertility and generates an important DLRF for nutrient uptake.
Keywords: Agroecosystem, Fertility, Organic Matter, Nitrogen, Depth